Pleiotropic effects of PPAR-α – from benchside to bedside - I. V. Shirinsky; V. S. Shirinsky (Медицинская иммунология)
Here we review literature data on properties of a member of nuclear hormone receptors - peroxisome proliferator-activated receptor-α. It was shown that PPARα was expressed on different cells including dendritic cells, macrophages, B- and T-cells. We discuss structure of natural and synthetic ligands of PPARa, molecular and cellular mechanisms of PPARa regulation of lipid and carbohydrate cellular metabolism. PPARa activity in hepatocytes results in decrease of intracellular concentrations of lipid acids. This leads to reduction of VLDL cholesterol, increase in HDL-cholesterol and decrease in triglycerides in plasma of patients taking PPARα agonists. Modulation of PPARa activity may change multiple biological effects of glucocorticoids (GCS) and insulin resistance. It is assumed that PPARα agonists reduce side effects of GCS and at the same time enhance their anti-inflammatory activity due to transrepression of NF-kB. We analyzed the results of several randomized studies, meta-analyses devoted to assessment of efficacy and safety of PPARa agonist fenofibrate in patients with type 2 diabetes mellitus with high risk of micro- and macrovascular events. The studies showed good safety profile of monotherapy with fibrates as well as of their combinations with statins, ezetimibe. Fibrates reduced not only cardiovascular events but also overall mortality. We present the data on the role of PPARa in control of glucose and lipid metabolism in subpopulations of innate and adaptive immunity cells. The data show that glucose and lipid metabolism play an important role in the fate of cells of innate and adaptive immunity. The metabolic state of lymphocytes has dynamic nature and depends on their functional activity. Transition from dormant cells with relatively low metabolism rate to activated and proliferating cells is accompanied with increase of metabolic demands. This transition is supported with the switch from oxidative metabolism to anaerobic glycolysis (Warburg effect) after antigen recognition by T-cells and B-cells. It was shown that granulocytes, dendritic cells and M1 macrophages were dependent on glucose metabolism during their activation while M2 macrophages were dependent on fatty acids oxidation. In contrast with lymphocytes, activated myeloid cells do not proliferate well but still have increased glycolysis which is necessary for their effector function. It is stressed that modulation of immune cells metabolism via PPARα gives new opportunities to modulate intensity and duration of immune responses in chronic diseases. We analyze studies performed on animal models of some chronic diseases, human patients with rheumatoid arthritis and different phenotypes of osteoarthritis. Most of the studies showed clinical efficacy and pleiotropic effects of PPARα agonists: antiinflammatory, immunomodulating and lipid modulating, primarily reduction of triglycerides and increase in HDL-C. The presented literature data suggest efficacy of PPARα agonists against individual components of polypathies. This could reduce risk of polypharmacy and reduce direct treatment costs. It is not unlikely that the use of PPARα agonists in a patient with multimorbidity could prevent acquiring a new disease. These are merely suggestions and much effort and time is required to perform large-scale randomized controlled studies evaluating new indications for the use of PPARa agonists.